2016
DOI: 10.1111/jcmm.12797
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking might weaken the prognostic significance of cytochrome P450 2C19*2 polymorphism in acute myocardial infarction patients

Abstract: Prognostic significance of cytochrome P450 2C19*2 polymorphism in acute myocardial infarction is still not well investigated. The aim of the study was to determine the relationship between the genetic polymorphism and the outcome of the acute myocardial infarction patients, and to further clarify the impact of smoking on such relationship. Six hundred acute myocardial infarction patients were enrolled. All of them provided blood samples and underwent clopidogrel treatment. The genetic polymorphism was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…25 Similarly, evidence for smoker's paradox was also seen in the present study after adjustment for age and comorbidity, consistent with previous studies. 26 Possible mechanisms include greater clopidogrel-induced platelet suppression, 27,28 and lower risk of adverse LV remodeling after infarction. 29 Because it is well-established that obesity and smoking are associated with long-term adverse event risk, we still recommend that patients maintain a BMI between 18.5 and 24.9 kg/m 2 and stop smoking after AMI, in accordance with the guideline.…”
Section: Obesity and Smoker's Paradoxesmentioning
confidence: 99%
“…25 Similarly, evidence for smoker's paradox was also seen in the present study after adjustment for age and comorbidity, consistent with previous studies. 26 Possible mechanisms include greater clopidogrel-induced platelet suppression, 27,28 and lower risk of adverse LV remodeling after infarction. 29 Because it is well-established that obesity and smoking are associated with long-term adverse event risk, we still recommend that patients maintain a BMI between 18.5 and 24.9 kg/m 2 and stop smoking after AMI, in accordance with the guideline.…”
Section: Obesity and Smoker's Paradoxesmentioning
confidence: 99%
“…Some studies have revealed that smoking could enhance the efficacy of clopidogrel and improve prognosis in patients with stroke or ACS ( 13 16 ). Other studies have shown that cigarettes may lower platelet activity during treatment, and weaken the outcomes significance of CYP2C19*2 in patients with ACS ( 16 , 17 ). Our study extended previous findings.…”
Section: Discussionmentioning
confidence: 97%
“…First, some studies showed that a suppressive effect of clopidogrel on platelets was greater in smokers than in non-smokers 27–29. A potential explanation for this finding is that smoking can enhance in-vivo bioactivation of clopidogrel via increasing induction of cytochrome P450 (CYP1A2 and CYP2B6) and increased active metabolite concentrations of clopidogrel 30 31.…”
Section: Discussionmentioning
confidence: 99%